Customer satisfaction towards Islamic banking in Malaysia: A study using Carter model - Lamsali, Hendrik; Ismail, Hirun Azaman; Che Razak, Razli; Mad Lazim, Halim; Adnan, Khairul Anuar; Ahmad Arshad, Darwina (2005)
This study has been carried out to determine potential differences in customers’ satisfaction towards Islamic banking (between geographical areas) in Malaysia. An alternative service quality measurement model called CARTER developed by Othman and Owen (2001) has been used particularly to address elements of compliance to Sharifah in addition to Parasuraman’s service quality measurement of five original dimensions. Data collection covering 5 largest cities from 5 states and four regions of peninsular Malaysia has been successfully conducted in which 1036 questionnaires have been returned. Respondents were randomly chosen from two of the largest banks in Malaysia in which one is Islamic bank and the latter is conventional bank offering Islamic banking scheme products and services. Descriptive statistics has been used to determine customers’ perception on elements of service quality while Analysis of Variance (ANOVA) has been applied to determine possible differences in customer satisfaction on Islamic banking between geographical areas (5 cities).